Enhanced thermotolerance of photosystem II by elevated pore-water salinity in the coastal marsh graminoid Sporobolus pumilus - Touchette, BW; Schmitt, SR; Moody, JWG (Aquatic Biology, 2020)
In coastal marsh ecosystems, high salinities, anoxic waterlogged soils, and elevated summer temperatures often promote physiological strain that results in only a few tolerant halophytic species. Although not well understood, plant physiological responses to multiple stressors can be complex and may involve intensifying or offsetting reactions. In this study, we investigated physiological responses to combined salinity and high temperature in the coastal marsh graminoid Sporobolus pumilus (syn. Spartina patens). Specifically, we considered changes in plant-water relations and Photosystem II (PSII) behavior (involving chlorophyll [chl] a fluorescence) in heat-shocked plants that were acclimated to different salinities (0, 15, and 30 psu). Higher salinities fostered lower stomatal conductance (g), lower leaf-water potential (Ψleaf) and lower tissue-water content (θ), as well as decreased potential quantum yield (Fv/Fm) and decreased excitation energy capture efficiencies of open reaction centers (Fv’/Fm’). Heat-shocked plants acclimated to freshwater only had decreased Fv/Fm and PSII performance index (PIABS). Interestingly, there were no changes in chl a fluorescent outputs in heat-shocked plants acclimated to moderate salinities, and minimal changes in plants acclimated to high salinities. Approximately 25% of the heat-shocked S. pumilus in freshwater revealed a K-step in their polyphasic chl a fluorescent transients (OJIP procedure); K-steps were not observed in salt-treated plants. This suggests that, for plants residing in freshwater, heat-shock promoted disturbances in the PSII reaction centers and, in some cases, disrupted the oxygen-evolving complex. These PSII disruptions were either absent or less intense in salinity-treated plants, indicating that acclimation to environmental salts may provide PSII thermostability in S. pumilus.